2018
DOI: 10.1007/s10086-018-1697-9
|View full text |Cite
|
Sign up to set email alerts
|

Study on the changes in surface characteristics of Populus tomentosa due to thermo-hydro-process

Abstract: The effects of high temperature, moisture, and mechanical action during the thermo-hydro-mechanical (THM) processing, on the changes in surface properties of poplar, namely, surface color, roughness, wettability, and microstructure, were investigated in this study. The correlation between observed changes in surface properties and chemical characteristics was also analyzed. Poplar woods with high moisture content were compressed using different pressures at temperature of 160 °C for four different periods. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…A prominent side effect of the applied process could be related to wood surface wettability. As reported by Song et al [17], wood wettability could be reduced since in the densified wood the fully collapsed wood cell walls are tightly intertwined along their cross-section and densely packed along their length direction [35,36]. Bektha and Krystofiak [37] showed that the contact angles of four densified wood species at a low temperature (100 °C-4MPA for 4 min) were lower than those of non-densified wood.…”
Section: Veneer Densitymentioning
confidence: 81%
“…A prominent side effect of the applied process could be related to wood surface wettability. As reported by Song et al [17], wood wettability could be reduced since in the densified wood the fully collapsed wood cell walls are tightly intertwined along their cross-section and densely packed along their length direction [35,36]. Bektha and Krystofiak [37] showed that the contact angles of four densified wood species at a low temperature (100 °C-4MPA for 4 min) were lower than those of non-densified wood.…”
Section: Veneer Densitymentioning
confidence: 81%
“…After unilateral surface densification, a large portion of wood fibers and vessels in the densified layer of USD-wood collapsed along the compression direction (Figure 3b,e), which could help increase the wood density, thus further improving the mechanical strength. Meanwhile, inhomogeneous compressive deformation of wood cells, primarily arising from the elastic buckling and plastic yielding of wood cell walls, 29 could be seen for the USD-wood, mainly depending on the lumen diameter, cell wall thickness, and cell shape. For the IUSD-wood impregnated at 30% concentration, the cell lumen in the densified layer almost disappeared after unilateral surface densification (Figure 3c,f), which is contributed by the plasticizing effect on wood cell walls caused by the acidic FA impregnation solution.…”
Section: Cell Morphology Of the Undensified And Densifiedmentioning
confidence: 99%
“…The texture of this black area was smooth. The black area was formed under high temperature and steam environment probably as a result of the thermo-hydro-process of wood powder [9].…”
Section: The Effect Of Water Contentmentioning
confidence: 99%